TIPE-TIPE KEPEMIMPINAN DALAM MANAJEMEN PENDIDIKAN - Leny Marlina (Ta'dib: Jurnal Pendidikan Islam, 2013)
Trust is a very significant thing in a management. Good management is supported by good leadership. Leadership stands on the foundation of trust. When confidence fragile, then the leader will soon collapse. Similar to a standing leadership in education on the basis of trust. Therefore, the most fundamental and important when being a leader is to instill confidence in the members or subordinates because of the way that a leader will be respected and honored in an organization. Planting a sense of trust in subordinates leadership is influenced by the type of person and the type of leadership style depends on the person.